What predicts the mobility of elementary schoolleaders? An analysis of longitudinal data in Colorado - Akiba, Motoko; Reichardt, Robert (Education Policy Analysis Archives, 2004)
While many studies have reported the predictors of teacher attrition, we know little about what predicts the attrition of school leaders. Using the Colorado state data on elementary school principals’ and assistant principals’ career paths from 1999 to 2001 and school achievement-level data, we addressed two research questions: 1) How do the age-specific attrition rates differ by gender and race? and 2) What other conditional factors are associated with the attrition of school leaders? We found that female and minority groups generally had higher attrition rates at age 40 or younger and at age 56 or older than male and non-minority groups. Our data also indicated that school size and salary increase were associated with the attrition of both male and female leaders. Large schools were more likely to have higher rates of school leader attrition, and the leaders who expected relatively higher salary increases by transferring were more likely to leave their schools. Lower school achievement predicted higher attrition of female leaders only. These findings have important implications for policy-makers when they plan and implement strategies for preventing high attrition rates of school leaders.